Deviation of Communication Ethics in Hospitals During the Covid 19 Pandemic Period March 2020 to January 2021 (Case Study at Menteng Mitra Afia Hospital) - RINALDI, Enrico Adhitya; LILIWERI, Alo; DUA, Mikhael; MULYASANTOSA, Nandang (PT Keberlanjutan Strategis Indonesia, 2023)
This study aims to analyze the Deviation of Communication Ethics seen from Medical Action Management Response and Communication Contravention. In this study, data was collected through an interview method with 10 health workers at Menteng Mitra Afia Hospital and 1 external resource person. The problem in this research is